Assessing the impact of chemo-mechanical and soxhlet extraction techniques on cellulose nanofiber characteristics - Muhammad Usman Zahid; Hifsa Zahid; Muhammad Usama Asghar; Waqas Khan Kayani; Aamir Rasheed; Faroha Liaqat; Faraz Muneer; Faiza Rasheed (PLoS ONE, 2025)
The extraction of cellulose nanofibers (CNFs) from lignocellulosic biomass provides a sustainable alternative to synthetic materials due to their biodegradability, mechanical strength, and environmental compatibility. However, conventional extraction methods are often affected by high chemical consumption, energy intensity, and limited scalability. This study presents a comparative and optimized approach for the sustainable extraction of CNFs using two distinct methods, including chemo-mechanical treatment and Soxhlet extraction, applied to sugarcane bagasse and eucalyptus bark. Unlike previous studies, this work systematically compares both methods under controlled conditions to evaluate their efficiency, fiber integrity, and environmental impact. The extracted CNFs were characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), dynamic light scattering (DLS), and zeta potential analysis. The FTIR spectra confirmed the presence of C–O–C fundamental vibrational stretching of cellulose and effective removal of non-cellulosic components such as lignin and hemicellulose. XRD results displayed the moderate crystalline nature of the extracted cellulose, with variation in intensity attributed to extraction technique and biomass type. Zeta potential analysis showed that CNFs extracted from eucalyptus bark via Soxhlet extraction exhibited superior colloidal stability (−32.5 mV), while those from sugarcane bagasse through chemo-mechanical treatment showed lower stability (−15.3 mV). These findings offer new insights into the method-material interaction and highlight the Soxhlet extraction route as more effective in producing stable, high-purity nanofibers. The protocols can be vital in reducing production costs and chemical utilization, enhancing material performance, and enabling large-scale application in packaging and biomedical industries.